Investigating the Managers Competency of Sports and Youth Offices in Alborz - Masoomeh Hamze; Sara Keshkar (Shahid Bahonar University of Kerman, 2020)
Competency of managers plays a critical role in the success of the organizations. The aim of this study was to investigate the competency of managers of Sports and Youth Offices in Alborz, Iran. 134 managers and staff of Sport and youth offices completed the researcher-developed questionnaire. Two questionnaires with 50 questions were used to get the research data, one questionnaire completed by managers and the other completed by staff. For validity, the questionnaires content were approved by 10 sports management experts, and their reliability were confirmed by Cronbachs alpha, respectively, 0.83 for the managers questionnaire and 0.90 for the staff questionnaire. Friedman, Kolmogorov-Smirnov, and t-test were conducted to test the research hypotheses. Result of the study shows that there is a significant difference between managers and Staff concerning communication skills, decision-making, encouragement, business communication, leadership, team development, and deployment of positive feature of the managers.